Numerical Simulation of Perkins Instability in the Midlatitude F-Region Ionosphere: The Influence of Background Ionospheric Multi-Factors - Yi Liu; Ting Lan; Yufeng Zhou; Yunzhou Zhu; Zhiqiang Fan; Yewen Wu; Yuqiang Zhang; Xiang Wang (Atmosphere)
A numerical simulation of Perkins instability in the midlatitude F-region ionosphere is developed in this study. The growth of nighttime plasma density perturbation excited by Perkins instability was successfully reproduced. The simulated results show that the ionospheric perturbation structure elongated from northwest (NW) to southeast (SE) was generated from initial random seeding by applying a very large southeastward neutral wind (200 m/s). The domain wave vector direction agreed with the linear Perkins theory. Our simulated results were consistent with the previous observations and simulations. To investigate the influence of background ionospheric multi-factors on the generation of nighttime medium-scale traveling ionospheric disturbance (MSTID), we simulated the evolution process of ionospheric perturbations under initial background ionospheric conditions. The simulated results indicate the importance of neutral scale height on the development of nighttime MSTID and suggest that a smaller neutral scale height would amplify the amplitude of ionospheric perturbations. The influences of gravity wave (GW) activity and polarized electric field seeding from plasma instability in the E region are also discussed in this study. We conclude that the additional seeding processes play a major role in the accelerated Perkins instability and amplify ionospheric perturbations. The electrodynamic coupling process has a greatly significant effect on the growth rate of Perkins instability compared to GW activity.